IMPLEMENTASI MANAJEMEN KELAS PADA PROGRAM MENTORING BINA PRIBADI ISLAM DI SD IT QURRATAA’YUN BATUSANGKAR - Rizki Febrian, Vicky; Yozi, Satri (JISPE Journal of Islamic Primary Education, 2022)
This research is a qualitative research conducted at SD IT Qurrata A'yun Batusangkar. The informants in this study were the Director and Student Representative of SD IT Qurrata A'yun and the Trustees of the Wihdatul Ummah Foundation. Data was collected through observation, interviews and documentation. The information obtained is analyzed in three steps, namely data reduction, data presentation, and drawing conclusions. Researchers use source triangulation. As well as the use of references to ensure the accuracy of the information. Based on the findings of the research results, it can be said that the implementation of management of the Islamic development program at SD IT Qurrata A'yun has been largely successful. However, supporting programs in the implementation of BPI, as well as policies related to the BPI program, must be more mature so that the program can achieve maximum goals.